CUNEOSPIRELLA SAMNITICA N. GEN. N. SP. (FORAMINIFERIDA) FROM THE SANTONIAN OF THE MATESE MOUNTAINS (MOLISE, CENTRAL ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
A new larger foraminifer, Cuneospirella samnitica n. gen., n. sp., from the Santonian of the Matese Mountains (central Italy) is described. This taxon, characterized by an initial planispiral, a rectilinear adult stage and the subdivision of chambers by partitions, could be descended from a morphotype like  Spiroplectammina multicamerata Said & Kenawy, recorded in the upper Turonian of the Apennines (central Italy).
Keywords: Cuneospirella; Foraminiferida; Systematics; Santonian; Matese Mountains; Central Italy